DEFINITION OF COMPOSITE THERMAL STABILITY at enterprises of aviation industry for their safe and effective application in heat-stressed units of new gen aircraft engines - A. V. Kopylov; B. V. Zubkov (Научный вестник МГТУ ГА)
The article deals with topical issues of development, introduction to businesses of aviation industry the experimental setup and test methods to determine the thermal stability of composites based on carbon materials (carbon fiber, matrix), which are the main structural material of heat-stressed components of aircraft engines of new generation. The article describes the ways of solving these problems.